Effect of different impression techniques and elastomeric impression materials on the dimensional accuracy of partially edentulous mandibular arch - Rafael Pino Vitti; Adriano Relvas Barreira de Oliveira; Mário Alexandre Coelho Sinhoreti (Universidade Estadual de Campinas, 2017)
Aim: Evaluate the dimensional accuracy of stone casts of a partially edentulous mandibular arch made by two impression techniques (1-step putty/light-body and 2-step putty/light-body) using addition and condensation silicones. Methods: A partially edentulous steel stainless cast with four markings on teeth 33, 37, 43, and 47 was used to obtain the impressions. The transverse (33-43 and 37-47) and anteroposterior (33-37 and 43-47) distances were measured by measuring microscope (30x magnification; 0.5μm accuracy). For the 1-step putty/light-body technique, both viscosities of the impression materials were handled together. For the 2-step putty/light-body technique, the impression materials of different viscosities were handled separately and a polypropylene spacer (2 mm thick) was used to create a relief. The same distances were measured om stone casts (n = 5). The values were submitted to normality test (Kolmogorov-Smirnov) and analyzed statistically by three-way ANOVA and Tukey's (5%). Results: All distances showed shrinkage (negative linear changes). The addition silicones showed better accuracy than condensation silicones (p<0.05) and no significant difference was found between the impression techniques (p>0.05). The edentulous zone (43-47) presented worst dimensional accuracy results. Conclusions: The accuracy of the castsis more related to the impression material than impression technique.